Influence of disease activity on functional capacity in patients with rheumatoid arthritis - Jovanović, Jelena Vladislav; Stojanović, Miodrag; Jovanović, Vladimir; Dimić, Aleksandar; Božilov, Sladjana; Stamenković, Bojana; Milenković, Saša (Vojnosanitetski pregled, 2014)
Background/Aim. Progressive erosive changes in cartilage  and bone in rheumatoid arthritis (RA) ultimately lead to joint deformities and disability which may be early, severe and permanent. Consequently, there is the reduction of functional ability and changes in the quality of life. The aim of this study was to estimate the impact of disease activity on functional status of patients with RA. Methods. A prospective investigation included 74 patients with RA who were treated in the Rheumatology Clinic of the “Niška Banja” Institute. Assessment of functional status (capacity) was measured by the Health Assessment Questionnaire (HAQ)  with the values from 0 to 3 that patients fill out on their own. The patients were then divided into three groups: the group I with the HAQ values from 0.125 to 1.000, the group II with the values from 1.125 to 2.000 and the group III with the values from 2.125 to 3.000. Disease activity was measured by Disease Activity Score (DAS28). The assessment also included sedimentation rate (SE) influence, IgM rheumatoid factor (RF) and C-reactive protein (CRP) positivity, age, and disease duration. Results. The patients with the most severe functional damage estimated by the HAQ – the group III, had the highest values of DAS28 SE (7.4 ± 0.8) compared to the group II (6.5 ± 1.2) and the group I (3.4 ± 1.2). The group III also showed the highest values of DAS28 CRP (7.1 ± 0.8) compared to the group II (6.7 ± 0.8) and the group I (3.6 ± 0.4). Compared with the patients with small and moderate functional damage, the patients in the group III had positive IgM RF and CRP as well as higher SE values more frequently and the difference was statistically significant. In the univariate logistic model, the tested parameters of DAS28 SE, DAS 28 CRP, SE, RF and CRP represent significant predictors of functional disability. The most significant factors that increase the odds of patient having the most severe functional damage include DAS28 SE which increases the odds by 5.5 times (OR = 5.450, 95% CI = 3.211–7.690, p = 0.001), DAS28 CRP by 5.1 times (OR = 5.111, 95% CI = 2.123–10.636, p < 0.01), and the presence of increased CRP (OR = 5.219, 95% CI = 1.305–18.231, p = 0.019) by 5.2 times. Conclusion. Functional status evaluated by the HAQ is a standard for assessment of RA due to its convenience and good correlation with parameters of disease activity. The most significant factors that increase the odds that the patient has the greatest functional damage are DAS28 SE, DAS28 CRP and the presence of CRP.
Keywords: arthritis; rheumatoid; severity of illness index; questionnaires; prognosis